Exploring how social media usage shapes self-presentation strategies among Saudi young adults - Muyidi, Ahmed (Frontiers in Psychology, 2025)
The rise of social networking sites (SNS) has changed how young people present themselves online to present idealized versions of their identities. These platforms enable selective self-presentation, shaped by features like anonymity and audience feedback. Especially in collectivist societies like Saudi Arabia, socio-cultural norms remain an effective factor, affecting online behaviors and leading to anonymous or semi-anonymous interactions. Despite the growing reliance on social networks, limited research addressed how these factors impact self-presentation strategies. This study examines how self-presentation on social media is affected by usage patterns among young adults in the Kingdom of Saudi Arabia. Using structured surveys, quantitative data are gathered from a sample of 715 young adults living countrywide. Results revealed that exemplification, ingratiation, and self-promotion are the most commonly used self-presentation strategies among Saudi youth. Negative usage patterns and a high number of followers used these strategies more frequently. Users disclosing users’ identities supported exemplification, reflecting cultural influences on online behaviors. Besides, increased time spent on social media was linked with greater use of all self-presentation strategies, highlighting potential risks to psychological well-being, i.e., anxiety and low self-esteem. Findings suggested a strong association between digital behaviors, audience dynamics, and impression management in a collectivist cultural context. Finally, cultural and clinical implications are presented, and limitations are highlighted.